Corn and forage sorghum yield and water use in Western Kansas - Waite, Jason (Kansas State University, 2016)
The Ogallala Aquifer is a large underground water source located under the High Plains and is used as the primary irrigation source for producers in the region. Hyper-extraction of the Ogallala is causing a reduction in irrigation capacity for a large part of the region. Confined animal feeding operations in western Kansas rely upon irrigated crops, mainly corn [Zea mays (L.)] as a source of feed. Research has shown that forage sorghum [Sorghum bicolor (L.) Monech] could meet the demands of the confined animal feeding operations while using less water than corn. An experiment was designed to evaluate corn and forage sorghum in Western Kansas. The objective of this research was to evaluate the water use and growth characteristics of irrigated and dryland corn and forage sorghum. Field experiments were conducted at two locations (Tribune Experiment Station, Tribune and a cooperator’s field near Hoxie, Sheridan County Kansas) in 2011-2013. The experimental design at Tribune was a randomized complete block with four replications. A traditional replicated design was not possible at Hoxie. Multiple subsamples per plot were obtained and data are reported as means with standard errors. Corn and forage sorghum were grown under both dryland and fully irrigated conditions at both locations. Neutron access tubes were installed to monitor soil water. Aboveground biomass, intercepted solar radiation and volumetric soil water content were recorded at 5 sampling dates each growing season. Water use was similar between irrigated corn and forage sorghum. There were differences in biomass from year to year between the irrigated crops. Dryland water use was similar between the two crops and also had differences in biomass from year to year. Yields were significantly lower than average for all crops in 2012 due to drought conditions. Solar radiation interception correlated with aboveground biomass measurements. Aboveground biomass from the forage sorghum and corn was ensiled both years and analyzed for nutrient composition. This research suggests that forage sorghum silage may be an acceptable replacement for corn silage in areas with reduced irrigation capacities.
Keywords: Corn; Forage; Sorghum; WaterOgallala Aquifer